2010
DOI: 10.1111/j.1445-2197.2010.05480.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency surgery for jejunal diverticulosis: our experience and review of literature

Abstract: Though rare, jejunal diverticulosis can present with several life-threatening complications that mandates immediate surgery. While the surgical procedure may be technically simple, achieving the accurate preoperative diagnosis is often fraught with challenges. CT scan could prove invaluable in the management if the situation permits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The mechanisms by which small bowel diverticular hemorrhage occurs are thought to be ulceration from diverticulitis or trauma to the mesenteric vessels [ 3 ]. Angiodysplasia, tumors, or parasitic infection [ 3 , 25 ] has also been reported to be associated with diverticular hemorrhage. In this series, both ulcers and Dieulafoy-like lesions were most commonly associated with bleeding, which suggested that standard endoscopic hemostatic techniques can also be applied in this setting [ 15 , 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which small bowel diverticular hemorrhage occurs are thought to be ulceration from diverticulitis or trauma to the mesenteric vessels [ 3 ]. Angiodysplasia, tumors, or parasitic infection [ 3 , 25 ] has also been reported to be associated with diverticular hemorrhage. In this series, both ulcers and Dieulafoy-like lesions were most commonly associated with bleeding, which suggested that standard endoscopic hemostatic techniques can also be applied in this setting [ 15 , 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its rarity, small bowel diverticulosis is often overlooked as a differential diagnosis. Bearing in mind that the complications of these diverticula can be catastrophic,5 it is worth considering them early in cases where there is diagnostic uncertainty. The importance in characterising jejunal diverticulae as opposed to other pathology, such as malignancy or Meckel’s diverticulum, lies in the possibility of difference in management.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is commonly overlooked when considering differential diagnoses. Complications arising from these diverticulae can be catastrophic with mortality rates reported as being as high as 24%–40% 4 5…”
Section: Introductionmentioning
confidence: 99%
“…Acute presentations of jejunal diverticula are rare, but very severe. The most common acute presentations include diverticulitis, hemorrhage or intestinal obstruction secondary to intussusception or volvulus [7] . Mechanical intestinal obstruction occurs in 2.3-4.6% of cases [2] .…”
Section: Discussionmentioning
confidence: 99%